2021
DOI: 10.7717/peerj.11110
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of apelin-13 against renal complications in L-NAME-induced preeclampsia in rats

Abstract: Pre-eclampsia (PE) accompanying acute liver and kidney injury has remained a master cause of both fetal and maternal mortality and morbidity. Vasoactive mediators, oxidative stress and inflammatory imbalanceshave an important role in PE pathogenesis. Apelin is an adipokine that improves endothelial dysfunction; has anti-inflammatory and antioxidant effects; moreover, its level reduced during PE. This study aimed to explore the effects of apelin-13 administration on preeclampsia-associated renal dysfunction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
3
12
0
2
Order By: Relevance
“…We showed that the body weight gain in dams was not affected by the administration of L-NAME from GD10 until a delivery. Notably, L-NAME treatment was able to cause a rise in systolic blood pressure in dams, even though the dose used in this experiment was relatively lower than that reported in the literature [25,26,[34][35][36][37]. A number of studies have shown that a similar effect of L-NAME is observed at higher doses [25][26][27].…”
Section: L-name Treatment Leads To No Deficiency In Dams and Their Offspringmentioning
confidence: 55%
“…We showed that the body weight gain in dams was not affected by the administration of L-NAME from GD10 until a delivery. Notably, L-NAME treatment was able to cause a rise in systolic blood pressure in dams, even though the dose used in this experiment was relatively lower than that reported in the literature [25,26,[34][35][36][37]. A number of studies have shown that a similar effect of L-NAME is observed at higher doses [25][26][27].…”
Section: L-name Treatment Leads To No Deficiency In Dams and Their Offspringmentioning
confidence: 55%
“…Probably, on the 15th day of pregnancy, vascular resistance in L-NAME-treated dams was increased as well, but its contribution to BP level was counterbalanced by the fall in the cardiac output, as seen from lower heart rate values. Of note, the treatment of animals with L-NAME is a commonly used model of preeclampsia [ 16 , 17 ]. In our model, we observed such manifestations of preeclampsia as increased blood pressure level and attenuated NO bioavailability [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, researchers showed that the administration of pyr-apelin-13 at 2 mg/kg body weight/day reduced blood pressure and normalised the heart rate in a rat PE model compared with controls, and also normalised proteinuria in association with lower renal cortical collagen deposition [ 145 ]. Moreover, apelin ameliorated kidney damage in a PE rat model; hence, it might represent a curative candidate for prohibiting kidney damage [ 146 ].…”
Section: Placental Pathology and Pregnancy Pathologymentioning
confidence: 99%